Misi Penginjilan Pada Masa Penciptaan dan Masa Kini - Desi Natalia (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2021)
The mission of evangelism at the time of creation in the biblical text of Genesis 1 and the mission of evangelism at this time, especially at GKE Hosianna Palangka Raya explain the two contexts that have colorful cultures, so that they require contextual stages, so that the mission of evangelism can be achieved. The method used is a qualitative method with a descriptive narrative approach, and uses an interpretive paradigm. Sources of data from interviews and literature studies related to evangelistic missions, the time of creation, and the present. The results showed that the congregation’s space and time were limited in the use of the Ngaju Dayak language liturgy both in its implementation and service implementation, so that the implementation of this liturgy was increasingly marginlized and it was necessary to make more innovative evangelistic strategies in responding to the covid-19 pandemic and after the covid-19 pandemic. The positive impact is being able to reduce the potential for the spread of covid-19, so that God’s relationship between family members becomes harmonious. Misi penginjilan pada masa penciptaan dalam teks Alkitab Kejadian 1 dan misi penginjilan pada masa kini, khususnya di GKE Hosianna Palangka Raya menerangkan kedua konteks yang memiliki kebudayaan yang berwarna-warni, sehingga memerlukan tahapan kontekstual, agar misi penginjilanpun dapat tercapai. Metode yang digunakan yaitu metode kualitatif dengan pendekatan deskriptif-naratif, serta menggunakan paradigma interpretatif. Sumber data dari hasil wawancara dan kajian literatur yang berkaitan dengan misi penginjilan, masa penciptaan, dan masa kini. Hasil penelitian menunjukkan ternyata ruang dan waktu jemaat menjadi terbatas dalam penggunaan liturgi bahasa Dayak Ngaju baik dalam pelaksanaan maupun pelaksana pelayanannya, sehingga penyelenggaraan liturgi ini semakin terpinggirkan dan perlu membuat strategi penginjilan yang lebih inovatif dalam menyikapi masa pandemi covid-19 dan setelah masa pandemi covid-19. Dampak positifnya yaitu mampu mengurangi potensi penyebaran covid-19, sehingga jemaat Tuhan dapat dalam keadaan sehat dan hubungan antara anggota keluarga menjadi harmonis.